The role of archaeological heritage in urban sites of Lithuania - Jurevičienė, Jūratė (Journal of Architecture and Urbanism, 2012)
The present paper aims to reveal current tendencies of archaeological heritage research as well as their presentation and interpretation in public spaces of historic centres of cities and towns in Lithuania. Such archaeological heritage is distinctive by its abundance, variety and authenticity. There are still many possibilities to reveal and present its value. Unfortunately, systematic and thorough archaeological investigations have not been conducted during the last two decades. The status of the state protected heritage site does not guarantee preservation of features that have cultural value. Archaic objects of archaeological heritage – such as castle mounds in historic centres of towns – require a more effective approach to integral preservation of both cultural and natural features. Discovered fragments of field-stone pavements are especially typical to excavations carried out during last decades. Nowadays, such preserved pavements serve their purpose in open spaces of urban centres. Presentation and interpretation of archaeological heritage still remain the most problematic aspects of preserved archaeological remains. The lack of systematic research, indeterminate responsibility for maintenance of public spaces, and private interests of investors result in poor reflection of archaeological value in the present architectural image particular to squares and streets of many historic urban sites of Lithuania. Article in Lithuanian. Archeologijos paveldo vaidmuo Lietuvos urbanistinėse vietovėse Santrauka. Nagrinėjamos archeologinio paveldo istoriniuose Lietuvos miestų ir miestelių centruose urbanistinės kraštovaizdinės vertės išsaugojimo, eksponavimo ir interpretavimo problemos. Analizuojami pastarųjų kelerių metų svarbesnieji archeologinių objektų ir kompleksų Lietuvos miestuose ir miesteliuose tyrimų bei tvarkybos pavyzdžiai. Atskleidžiami archeologinių darinių vertės aspektai, lemiantys urbanistinėje aplinkoje išlikusio archeologinio paveldo kultūrinį pažintinį potencialą. Siekiama atskleisti dabartiniame Lietuvos miestų ir miestelių istorinių branduolių formavimo laikotarpiu archeologinėms kultūrinėms vertybėms iškylančias grėsmes ir jų pritaikymo galimybes kuriant darnią aplinką. Reikšminiai žodžiai: archeologinis paveldas, Lietuvos miestai ir miesteliai, istorinis centras, interpretavimas.